The equations of the inserted length of percutaneous central venous catheters on neonates in NICU - I-Lun Chen; Mei-Chen Ou-Yang; Feng-Shun Chen; Mei-Yung Chung; Chih-Cheng Chen; Yu-Chen Liu; Kuan-Hung Lin; Hsin-Chun Huang (Pediatrics and Neonatology)
Background: In neonatal intensive care units, a percutaneous central venous catheter (PCVC) is inserted peripherally and threaded into a central venous location, when intravenous access is anticipated for an extended period of time. The tip location of PCVCs should be checked by an X-ray after the procedure. The present study aimed to determine an equation to estimate the optimal insertion length of PCVCs in neonates prior to the procedure. Methods: The data of all neonates who had PCVC insertion between May 1st 2015 and April 30th 2016 was reviewed. Their gender, body weight and body length at the insertion date, any complications and the tip culture of their PCVCs were recorded. The tip location of the PCVC, which was confirmed by X-ray, was either in the inferior vena cava near to the diaphragm or in the superior vena cava before the right atrial junction, depending on the insertion site. We analyzed the correlation among inserted length of PCVCs, body weight and body length by linear regression to determine an equation for estimating the optimal insertion length of PCVCs. The accuracy of the equations was evaluated prospectively by Pearson's correlation analysis, and the adjusting rate of PCVCs after the initial insertion was compared between the traditional method and using the equation. Results: The equation of PCVCs inserted in the foot was “insertion length (cm) = 16 + 4.27 × body weight (kg)”, in the femoral vein was “inserted length (cm) = 9.8 + 1.7 × body weight (kg)”, in the popliteal vein was “inserted length (cm) = −0.3 + 0.45 × body length (cm)”, in the hand was “inserted length (cm) = 4.46 + 0.32 × body length (cm)”, and in the axillary vein was inserted length (cm) = 1 + 0.18 × body length (cm). The adjusting rate of PCVCs after initial insertion was decreased from 73.5% to 53% following use of the equation. Conclusions: Equations provided a convenient and accurate method to estimate the optimal insertion length of PCVCs before their placement. Key Words: equation, intensive care, neonate, PICC